Ribosomal distribution in a polyamine auxotroph of Escherichia coli. - Algranati, I D (1975)
The distribution of ribosomal particles has been studied in a polyamine-deficient mutant of Escherichia coli by sucrose gradient centrifugation analysis. Lysates from starved cells contained less 70S monomers and 30S subunits but more 50S particles than those prepared from bacteria supplemented with putrescine. The addition of the polyamine to putrescine-depleted cells induced a rapid change of the ribosomal profile. A similar effect could be obtained in vitro by equilibrium dialysis against a polyamine-containing solution. The ribosomal pattern obtained from starved bacteria was specific for polyamine deficiency. We conclude that the changes in ribosomal profiles upon restoration of putrescine levels in previously starved cells denote a shift of the equilibrium between 30S-50S couples and ribosomal subunits.